Pemberian Rational Emotive Behavior Therapy Dalam Mengontrol Perilaku Agresif Pada Pasien Perilaku Kekerasan - Rilarahmawati Thalib; Rusli Abdullah (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: Violent behavior is one of the symptoms of mental disorders that can trigger physical harm to patients and others. Aims: To determine the provision of Rational Emotive Behavior Therapy (REBT) in controlling aggressive behavior in patients with violent behavior. Methods: This review uses a literature review approach. Sources of data obtained through article search results using four databases, namely Pubmed, Proquest, Garuda, and Google Scholar identified 26,083 articles. The analysis uses a map of the extracted data in a grid synthesis table including author, year, country, purpose, sample, design, duration, results, and conclusions of the study. Results: Four articles identified in this review showed that before REBT therapy was given, most of the patients were unable to control aggressive behavior as indicated by a high mean risk score for aggressive behavior, both cognitive, affective, social, and physiological, but after REBT therapy most of the patients were able to control aggressive behavior. characterized by a significant change in the symptoms of the risk of violent behavior experienced by the patient. Conclusion: Based on the results of a review of four articles, it was concluded that the administration of REBT could significantly improve the patient's ability to control violent behavior in aggressive behavior characterized by changes in the patient's cognitive, affective, social, and physiological responses